On variation of eigenvalues of birth and death matrices and random walk matrices - Castillo, K. (2022)
The purpose of this note is twofold: firstly to improve the known results on variation of extreme eigenvalues of birth and death matrices and random walk matrices; and secondly to progress towards the solution of a thirty years old open problem concerning the variation of eigenvalues of these matrices. © 2022 Elsevier Inc.